Temporally and spatially controlled induction of gene expression in Arabidopsis thaliana - Maizel, Alexis; Weigel, Detlef (The plant journal, 2004)
Temporally and spatially regulated induction of gene expression is an important tool of genetic analysis. In plants, several systems are available for spatially unregulated induction of gene expression, or for spatially regulated expression. Here, we describe a new system that provides both temporal and spatial control for transgene expression. It combines the advantages of its two constituent components: temporally regulated activity of the ethanol-dependent AlcR transcription factor, and tissue specificity of a plant promoter. As a proof of principle, transgenic lines were developed in which the promoter of the meristem identity gene LEAFY (LFY) provided flower-specific expression of the AlcR activator. Tissue-specific activity of AlcR was confirmed with a responder in which the β-glucuronidase (GUS) reporter was under the control of the alcA response element. As expected, reporter activity in a pattern typical for the LFY promoter was ethanol dependent. Next, we placed the LFY coding sequenced under control of the AlcA response element. In a strong lfy-12 background, this construct in combination with the LFY:AlcR driver provided complete, ethanol-dependent rescue of the lfy phenotype, including restoration of fertility. Apart from facilitating the investigation of temporal and spatial requirements of gene activity, this technology will permit new types of genetic modifier screens starting with mutations that otherwise confer lethality or sterility.